Moisture-conducting cool-feeling fabric for sportswear and preparation method of moisture-conducting cool-feeling fabric

By reacting the modified spinning fiber with hydrogen-containing silicone oil and treated with 3-bromopropyl trimethyl ammonium bromide, we form a wet-guiding and cool-sensing fabric for sports clothing, solving the problems of insufficient moisture-guiding and antibacterial properties of existing fabrics, and achieving good performance of sports clothing fabrics.

CN119531137AInactive Publication Date: 2025-02-28GUANGDONG XIANGQIFU IND CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510107174.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-02-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing sports clothing fabrics are difficult to effectively guide moisture and provide a cool feeling during exercise, and are prone to bacterial growth.

Method used

Modified spinning fibers are used to react with hydrogen-containing silicone oil to obtain the precursor fabric, and then react with 3-bromopropyltrimethylammonium bromide to form a wet-induced cool-sensing fabric. The fabric improves antibacterial and flame retardant properties through zinc-loaded ions and polymerized grafting reactions.

Benefits of technology

It achieves good moisture-guiding and cool-sensing effects of sports clothing fabrics, while improving antibacterial and flame retardant properties, and extending the service life of the fabric.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_6
    Figure SMS_6
  • Figure SMS_7
    Figure SMS_7
Patent Text Reader

Abstract

The invention discloses a moisture-conducting cool-feeling fabric for sportswear and a preparation method of the moisture-conducting cool-feeling fabric, and relates to the field of fabrics. When the moisture-conducting cool-feeling fabric for sportswear is prepared, zinc ions are loaded on porous nanometer aluminum oxide, then chloromethyl trimethoxy silane is grafted, and modified zinc-loaded nanometer aluminum oxide is obtained through a reaction with 2, 6-pyridine dimethyl carbinol and 3, 6-dichloro-4-vinylpyridazine; reacting dimethyl terephthalate, a modified monomer and ethylene glycol to obtain a modified polyester chip; uniformly mixing the modified polyester chips, the modified zinc-loaded nano aluminum oxide and polyethylene glycol 2000, and spinning to obtain spinning fibers; the preparation method comprises the following steps: reacting spinning fibers with hydrogen-containing silicone oil, weaving to obtain a precursor fabric, and reacting with 3-bromopropyl trimethyl ammonium bromide to obtain the moisture-conducting cool-feeling fabric for sportswear. The moisture-conducting cool fabric for sportswear prepared by the invention has excellent moisture-conducting cool, flame-retardant, antibacterial and mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of fabrics, in particular to a moisture-conducting cool fabric for sportswear and a preparation method thereof. Background Art

[0002] With the development of the economy, people's dressing concept has changed. The demand for clothes is no longer simply the pursuit of their appearance and durability, but the hope that the clothes they wear have better comfort. The comfort of clothing is coordinated and acted upon by a variety of environmental factors, people's natural activity state and the characteristics of the clothing itself. The comfort of fabrics is divided into several different aspects, including psychological comfort, pressure comfort, physiological comfort, and thermal and moist comfort. They have different focuses but complement each other. In the process of studying comfort, thermal and moist comfort is a crucial part. A microenvironment of heat and moisture transfer can be generated between people and the environment. In this microenvironment, fabrics can maintain the body temperature balance of the human body, provide the human body with a good thermal and moist condition, ensure the normal and stable physiological functions of the human body, and maintain the human body's comfort.

[0003] In recent years, the country has proposed a national fitness plan, and the concept of national sports and daily sports has been deeply rooted in the hearts of the people. People's attention to health and safety issues continues to increase, and they have higher requirements for clothing and commodities. Many researchers have improved the design concept of textiles and paid more attention to the comfort, functionality and fashion of textiles. When people exercise, they will inevitably have the trouble of hot and sweating, and clothes are prone to breed bacteria after being stained with sweat. Therefore, the present invention prepares a moisture-conducting and cool fabric for sportswear with excellent antibacterial properties. Summary of the invention

[0004] The object of the present invention is to provide a moisture-conducting and cool fabric for sportswear and a preparation method thereof, so as to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a moisture-conducting and cooling fabric for sportswear, wherein the moisture-conducting and cooling fabric for sportswear is obtained by weaving a precursor fabric by reacting spun fibers with hydrogen-containing silicone oil, and then reacting with 3-bromopropyltrimethylammonium bromide; as an optimization, the spun fibers are obtained by mixing and spinning modified polyester chips, modified zinc-loaded nano-alumina and polyethylene glycol 2000.

[0006] As an optimization, the polyethylene glycol 2000 comes from Shandong Baihua Chemical Co., Ltd.

[0007] As an optimization, the modified polyester chips are obtained by reacting diethyl (formylmethyl) phosphate with 4-methylpyridine, and then reacting with dimethyl terephthalate and ethylene glycol.

[0008] As an optimization, the modified zinc-loaded nano-alumina is prepared by loading zinc ions onto porous nano-alumina, grafting chloromethyltrimethoxysilane, and then reacting with 2,6-pyridine dimethanol and 3,6-dichloro-4-vinylpyridazine.

[0009] As an optimization, the porous nano-alumina model is 30 nanometers and comes from Hangzhou Jiupeng New Materials Co., Ltd.

[0010] A method for preparing a moisture-conducting and cool fabric for sportswear, comprising the following preparation steps: (1) Mix zinc-loaded nano-alumina, chloromethyltrimethoxysilane and anhydrous ethanol in a mass ratio of 1: (0.01-0.02): (10-20), ultrasonically disperse for 20-30 min, stir at 70-90 °C and 100-200 rpm for 4-6 h, cool naturally to room temperature and filter, and dry at 40-50 °C for 4-6 h to obtain pre-modified zinc-loaded nano-alumina; mix pre-modified zinc-loaded nano-alumina, 2,6-pyridine dimethanol, 3,6-dichloro-4-vinylpyridazine, sodium hydroxide and deionized water in a mixture of 1: (0.01-0.02): (10-20) to obtain a pre-modified zinc-loaded nano-alumina; Mass ratio 1: (1-2): (1.7-1.9): (4-6): (950-1050) mixed, ultrasonicated for 25-35 minutes, stirred at 30-40°C and 100-200 rpm for 5-7 hours, added 36%-38% hydrochloric acid solution with a mass fraction of 10-20 times the mass of the pre-modified zinc-loaded nano-alumina, ultrasonicated again for 25-35 minutes and then filtered, washed with deionized water and anhydrous ethanol for 3-5 times respectively, dried at 60-70°C for 11-13 hours, and obtained modified zinc-loaded nano-alumina; (2) Mix diethyl (formylmethyl) phosphate, 4-methylpyridine and n-butanol in a mass ratio of 1: (0.5-0.6): (6-8), heat to 105-115°C at 300-400 rpm in a nitrogen atmosphere, add pyridine in an amount of 0.1-0.3 times the mass of diethyl (formylmethyl) phosphate, continue stirring for 79-81 hours, add deionized water in an amount of 100-200 times the mass of diethyl (formylmethyl) phosphate, stir until the mass of the precipitated solid remains unchanged, filter, grind and sieve 40-60 mesh, wash with acetone 3-5 times, and dry at 50-60°C for 12-14 hours to obtain a modified monomer; (3) Mix dimethyl terephthalate, modified monomer, ethylene glycol and ethylene glycol antimony in a mass ratio of 1: (0.6-0.8): (0.5-0.7): (0.01-0.03), heat at 140-150°C for 20-30 min, heat to 175-185°C, stir at 75-85 rpm for 1-3 h, heat to 240-260°C, stir under vacuum for 20-30 min, cool naturally to room temperature, take out slices to obtain modified polyester slices; mix the modified polyester slices, modified zinc-loaded nano-alumina and polyethylene glycol 2000 in a mass ratio of 1: (0.02-0.04): (0.01-0.02), and perform melt spinning using a multifunctional flexible high-speed spinning machine to obtain spun fibers; (4) Mix hydrogen-containing silicone oil and chloroplatinic acid in a mass ratio of 1:(0.01-0.03) to obtain a hydrogen-containing silicone oil finishing solution; soak the spun fiber in the hydrogen-containing silicone oil finishing solution for 1-2 hours, take it out, let it stand at 70-80°C for 6-8 hours, wash it with deionized water for 3-5 times, and dry it at 55-65°C for 8-10 hours to obtain a modified fiber; twist the modified fiber together, and weave it in plain weave on a small sample loom to obtain a precursor fabric; spray a 1%-2% mass fraction of 3-bromopropyltrimethylammonium bromide aqueous solution on the outer surface of the precursor fabric, stand it at 60-70°C for 11-13 hours, wash it with deionized water for 3-5 times, and dry it at 55-65°C for 12-14 hours to obtain a moisture-conducting and cool fabric for sportswear.

[0011] As an optimization, the zinc-loaded nano-alumina in step (1) is prepared by mixing porous nano-alumina powder and ethylene glycol in a mass ratio of 1:(95-105), adding 9-11 mol / L sodium hydroxide solution to adjust the pH to 7.5-8.5, ultrasonically dispersing for 25-35 min, adding saturated zinc nitrate alcohol solution 20-30 times the mass of the porous nano-alumina powder, stirring at 45-55° C. and 100-200 rpm for 7-9 h, naturally cooling to room temperature and then centrifuging, washing with anhydrous ethanol for 3-5 times, and drying at 45-55° C. for 8-10 h.

[0012] As an optimization, the reaction equation of the pre-modified zinc-loaded nano-alumina in step (1) is: .

[0013] As an optimization, the reaction equation for modifying the zinc-loaded nano-alumina in step (1) is: .

[0014] As an optimization, the reaction equation of the modified monomer in step (2) is: .

[0015] As an optimization, the reaction equation of the modified polyester chips in step (3) is: .

[0016] As an optimization, the melt spinning parameters of step (3) are as follows: spinneret hole number 35~37 holes, side blowing power 9~11 Hz, oil pump power 19~21 Hz, assembly pressure 6~9 MPa, winding speed 750~850 m / min, zone 1 245~255°C, zone 2 275~285°C, zone 3 275~285°C, metering pump temperature 275~285°C, elbow temperature 275~285°C, box temperature 275~285°C.

[0017] As an optimization, the reaction equation of the moisture-conducting and cool fabric for sportswear in step (4) is: .

[0018] As an optimization, the weaving parameters of step (4) are: linear density 76-78, warp density 550-650 strands / 10 cm, and weft density 360-400 strands / 10 cm.

[0019] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: when preparing the moisture-conducting and cooling fabric for sportswear, the porous nano-alumina is loaded with zinc ions and then grafted with chloromethyltrimethoxysilane, and then reacted with 2,6-pyridine dimethanol and 3,6-dichloro-4-vinylpyridazine to obtain modified zinc-loaded nano-alumina; diethyl (formylmethyl) phosphate is reacted with 4-methylpyridine to obtain a modified monomer; dimethyl terephthalate, the modified monomer and ethylene glycol are reacted to obtain a modified polyester slice; the modified polyester slice, the modified zinc-loaded nano-alumina and polyethylene glycol 2000 are mixed and spun to obtain spun fibers; the spun fibers are reacted with hydrogen-containing silicone oil to obtain a precursor fabric, and then reacted with 3-bromopropyltrimethylammonium bromide to obtain a moisture-conducting and cooling fabric.

[0020] First, porous nano-alumina is loaded with zinc ions and then grafted with chloromethyltrimethoxysilane, and then reacted with 2,6-pyridine dimethanol and 3,6-dichloro-4-vinylpyridazine to obtain modified zinc-loaded nano-alumina; diethyl (formylmethyl) phosphate is reacted with 4-methylpyridine to obtain a modified monomer; dimethyl terephthalate, the modified monomer and ethylene glycol are then reacted to obtain a modified polyester slice; porous nano-alumina with high thermal conductivity is used as a reinforcing phase to enhance the thermal conductivity of the moisture-conducting and cool fabric and strengthen the cool effect; zinc ions are then loaded in the pores, and the zinc ions are used to interact with the negative ions of bacterial cells to cause abnormal enzyme and protein mechanisms in the bacterial cells, destroy cell metabolism, and improve the antibacterial property of the moisture-conducting and cool fabric ; 2,6-pyridine dimethanol and 3,6-dichloro-4-vinylpyridazine are polymerized and grafted on the surface of porous nano-alumina. The pyridine ring can complex zinc ions to achieve a sustained release effect, thereby improving the long-lasting antibacterial properties of the moisture-conducting and cool fabric. During the combustion process, the pyridazine ring can produce nitrides, nitrogen-containing free radicals and other substances, which react with the free radicals in the combustion process to inhibit the continuation of the combustion reaction and improve the flame retardant properties of the moisture-conducting and cool fabric. A modified monomer containing a carbon-carbon double bond is obtained by condensing methyl and formaldehyde under the catalysis of pyridine, participating in the polymerization of the polyester main chain, introducing phosphorus, and reacting with the free radicals generated during the combustion process to form a stable carbon layer, blocking oxygen, inhibiting the spread of flames, and further improving the flame retardant properties of the moisture-conducting and cool fabric.

[0021] Secondly, the modified polyester chips, modified zinc-loaded nano-alumina and polyethylene glycol 2000 are mixed and spun to obtain spun fibers; the spun fibers are reacted with hydrogen-containing silicone oil to obtain a precursor fabric, which is then reacted with 3-bromopropyltrimethylammonium bromide to obtain a moisture-conducting and cool fabric; polyethylene glycol 2000 is used as a porogen to form a pore structure to improve the moisture-conducting and cool fabric; the spun fibers are post-finished with hydrogen-containing silicone oil, and the modified polyester chips and the modified zinc-loaded nano-alumina are reacted with the hydrogenated silicone oil by a silylation reaction. The carbon-carbon double bonds react to form a cross-linked network, which improves the mechanical properties of the moisture-conducting and cool fabric. The finishing with hydrogen silicone oil also enhances the hydrophobic ability of the fiber. After the fabric is woven, it is single-sided finished with 3-bromopropyltrimethylammonium bromide, and the trimethylammonium bromide ion is used as the hydrophilic end to form a unidirectional moisture-conducting structure with a hydrophobic inner layer and a hydrophilic outer layer, further improving the moisture-conducting and cool fabric. At the same time, nitrogen heterocyclic quaternary ammonium salts are formed to increase the positive charge density, enhance the antibacterial activity, and further improve the antibacterial properties of the moisture-conducting and cool fabric. DETAILED DESCRIPTION

[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0023] Example 1 A method for preparing a moisture-conducting and cooling fabric for sportswear, the method comprising the following preparation steps: (1) The porous nano-alumina powder and ethylene glycol were mixed at a mass ratio of 1:95, 9 mol / L sodium hydroxide solution was added to adjust the pH to 7.5, ultrasonic dispersion was performed for 25 min, saturated zinc nitrate alcohol solution of 20 times the mass of the porous nano-alumina powder was added, stirred at 45°C and 100 rpm for 9 h, cooled naturally to room temperature and centrifuged, washed with anhydrous ethanol for 3 times, and dried at 45°C for 10 h to obtain zinc-loaded nano-alumina; zinc-loaded nano-alumina, chloromethyltrimethoxysilane and anhydrous ethanol were mixed at a mass ratio of 1:0.01:10, ultrasonic dispersion was performed for 20 min, and stirred at 70°C and 100 rpm for 6 h , naturally cooled to room temperature and then filtered, dried at 40°C for 6h to obtain pre-modified zinc-loaded nano-alumina; pre-modified zinc-loaded nano-alumina, 2,6-pyridine dimethanol, 3,6-dichloro-4-vinyl pyridazine, sodium hydroxide and deionized water were mixed in a mass ratio of 1:1:1.7:4:950, ultrasonicated for 25min, stirred at 30°C and 100rpm for 7h, and a 36% hydrochloric acid solution with a mass fraction of 10 times the mass of the pre-modified zinc-loaded nano-alumina was added, ultrasonicated again for 35min and then filtered, washed with deionized water and anhydrous ethanol for 3 times respectively, and dried at 60°C for 13h to obtain modified zinc-loaded nano-alumina; (2) Mix diethyl (formylmethyl) phosphate, 4-methylpyridine and n-butanol in a mass ratio of 1:0.5:6, heat to 105°C at 300 rpm in a nitrogen atmosphere, add pyridine in an amount of 0.1 times the mass of diethyl (formylmethyl) phosphate, continue stirring for 81 hours, add deionized water in an amount of 100 times the mass of diethyl (formylmethyl) phosphate, stir until the mass of the precipitated solid remains unchanged, filter, grind and sieve 40 mesh, wash with acetone three times, and dry at 50°C for 14 hours to obtain a modified monomer; (3) Dimethyl terephthalate, modified monomer, ethylene glycol and ethylene glycol antimony were mixed in a mass ratio of 1:0.6:0.5:0.01, heated at 140°C for 30 min, heated to 175°C, stirred at 75 rpm for 3 h, heated to 240°C and stirred in vacuum for 30 min, naturally cooled to room temperature, and sliced ​​to obtain modified polyester slices; modified polyester slices, modified zinc-loaded nano-alumina and polyethylene glycol 2000 were mixed in a mass ratio of 1:0.02:0.01, and melt-spun using a multifunctional flexible high-speed spinning machine at 245°C in zone 1, 275°C in zone 2, 275°C in zone 3, 275°C in metering pump temperature, 275°C in elbow temperature, 275°C in box temperature, 35 spinneret holes, 9Hz in side blowing power, 19Hz in oil pump power, 6MPa in assembly pressure, and 750m / min in winding speed to obtain spun fibers; (4) Hydrogen-containing silicone oil and chloroplatinic acid are mixed in a mass ratio of 1:0.01 to obtain a hydrogen-containing silicone oil finishing solution; the spun fiber is soaked in the hydrogen-containing silicone oil finishing solution for 1 hour and then taken out, aired until no liquid drops for 10 seconds, allowed to stand at 70°C for 8 hours, washed with deionized water for 3 times, and dried at 55°C for 10 hours to obtain a modified fiber; the modified fiber is twisted and woven on a small sample loom under the conditions of a line density of 76, a warp density of 550 strands / 10cm, and a weft density of 360 strands / 10cm to obtain a precursor fabric; a 1% mass fraction of 3-bromopropyltrimethylammonium bromide aqueous solution is sprayed on the outer surface of the precursor fabric, allowed to stand at 60°C for 13 hours, washed with deionized water for 3 times, and dried at 55°C for 14 hours to obtain a moisture-conducting and cool fabric for sportswear.

[0024] Example 2 A method for preparing a moisture-conducting and cooling fabric for sportswear, the method comprising the following preparation steps: (1) Porous nano-alumina powder and ethylene glycol were mixed at a mass ratio of 1:100, 10 mol / L sodium hydroxide solution was added to adjust the pH to 8, ultrasonic dispersion was performed for 30 min, saturated zinc nitrate alcohol solution of 25 times the mass of porous nano-alumina powder was added, stirred at 50°C and 150 rpm for 8 h, cooled naturally to room temperature and centrifuged, washed with anhydrous ethanol for 4 times, and dried at 50°C for 9 h to obtain zinc-loaded nano-alumina; zinc-loaded nano-alumina, chloromethyltrimethoxysilane and anhydrous ethanol were mixed at a mass ratio of 1:0.015:15, ultrasonic dispersion was performed for 25 min, stirred at 80°C and 150 rpm for 5 h, and dried at 50°C for 9 h. Then cool to room temperature and filter, dry at 45°C for 5h to obtain pre-modified zinc-loaded nano-alumina; mix the pre-modified zinc-loaded nano-alumina, 2,6-pyridine dimethanol, 3,6-dichloro-4-vinyl pyridazine, sodium hydroxide and deionized water in a mass ratio of 1:1.5:1.8:5:1000, ultrasonicate for 30min, stir at 35°C and 150rpm for 6h, add a 37% hydrochloric acid solution with a mass fraction of 15 times the mass of the pre-modified zinc-loaded nano-alumina, ultrasonicate for 30min again, filter, wash with deionized water and anhydrous ethanol for 4 times respectively, and dry at 65°C for 12h to obtain modified zinc-loaded nano-alumina; (2) Mix diethyl (formylmethyl) phosphate, 4-methylpyridine and n-butanol in a mass ratio of 1:0.55:7, heat to 110°C at 350 rpm in a nitrogen atmosphere, add pyridine in an amount of 0.2 times the mass of diethyl (formylmethyl) phosphate, continue stirring for 80 h, add deionized water in an amount of 150 times the mass of diethyl (formylmethyl) phosphate, stir until the mass of the precipitated solid remains unchanged, filter, grind and sieve 50 mesh, wash with acetone 4 times, and dry at 55°C for 13 h to obtain a modified monomer; (3) Dimethyl terephthalate, modified monomer, ethylene glycol and ethylene glycol antimony were mixed in a mass ratio of 1:0.7:0.6:0.02, heated at 145°C for 25 min, heated to 180°C, stirred at 80 rpm for 2 h, heated to 250°C and stirred in vacuum for 25 min, cooled naturally to room temperature, and sliced ​​to obtain modified polyester slices; modified polyester slices, modified zinc-loaded nano-alumina and polyethylene glycol 2000 were mixed in a mass ratio of 1:0.7:0.6:0.02. 0.03:0.015 was mixed, and melt spinning was performed using a multifunctional flexible high-speed spinning machine at 250°C in the first zone, 280°C in the second zone, 280°C in the third zone, 280°C in the metering pump, 280°C in the elbow, 280°C in the box, 36 holes in the spinneret, 10Hz in the side blowing power, 20Hz in the oil pump power, 7.5MPa in the component pressure, and 800m / min in the winding speed to obtain spun fibers; (4) Hydrogen-containing silicone oil and chloroplatinic acid are mixed in a mass ratio of 1:0.02 to obtain a hydrogen-containing silicone oil finishing solution; the spun fiber is soaked in the hydrogen-containing silicone oil finishing solution for 1.5 hours and then taken out, aired until no liquid drops for 15 seconds, allowed to stand at 75°C for 7 hours, washed with deionized water for 4 times, and dried at 60°C for 9 hours to obtain a modified fiber; the modified fiber is twisted and twisted, and plain woven on a small sample loom under the conditions of an online density of 77, a warp density of 600 strands / 10cm, and a weft density of 380 strands / 10cm to obtain a precursor fabric; a 1.5% mass fraction of 3-bromopropyltrimethylammonium bromide aqueous solution is sprayed on the outer surface of the precursor fabric, allowed to stand at 65°C for 12 hours, washed with deionized water for 4 times, and dried at 60°C for 13 hours to obtain a moisture-conducting and cool fabric for sportswear.

[0025] Example 3 A method for preparing a moisture-conducting and cooling fabric for sportswear, the method comprising the following preparation steps: (1) The porous nano-alumina powder and ethylene glycol were mixed at a mass ratio of 1:105, 11 mol / L sodium hydroxide solution was added to adjust the pH to 8.5, ultrasonic dispersion was performed for 35 min, 30 times the mass of the porous nano-alumina powder was added with a saturated zinc nitrate alcohol solution, stirred at 55°C and 200 rpm for 7 h, cooled naturally to room temperature and centrifuged, washed with anhydrous ethanol for 5 times, and dried at 55°C for 8 h to obtain zinc-loaded nano-alumina; zinc-loaded nano-alumina, chloromethyltrimethoxysilane and anhydrous ethanol were mixed at a mass ratio of 1:0.02:20, ultrasonic dispersion was performed for 30 min, and stirred at 90°C and 200 rpm for 4 h , naturally cooled to room temperature and then filtered, dried at 50°C for 4h to obtain pre-modified zinc-loaded nano-alumina; pre-modified zinc-loaded nano-alumina, 2,6-pyridine dimethanol, 3,6-dichloro-4-vinyl pyridazine, sodium hydroxide and deionized water were mixed in a mass ratio of 1:2:1.9:6:1050, ultrasonicated for 35min, stirred at 40°C and 200rpm for 5h, and a hydrochloric acid solution with a mass fraction of 38% of 20 times the mass of the pre-modified zinc-loaded nano-alumina was added, ultrasonicated again for 25min and then filtered, washed with deionized water and anhydrous ethanol for 5 times respectively, and dried at 70°C for 11h to obtain modified zinc-loaded nano-alumina; (2) Mix diethyl (formylmethyl) phosphate, 4-methylpyridine and n-butanol in a mass ratio of 1:0.6:8, heat to 115°C at 400 rpm in a nitrogen atmosphere, add pyridine in an amount of 0.3 times the mass of diethyl (formylmethyl) phosphate, continue stirring for 79 hours, add deionized water in an amount of 200 times the mass of diethyl (formylmethyl) phosphate, stir until the mass of the precipitated solid remains unchanged, filter, grind and sieve 60 mesh, wash with acetone 5 times, and dry at 60°C for 12 hours to obtain a modified monomer; (3) Dimethyl terephthalate, modified monomer, ethylene glycol and ethylene glycol antimony were mixed in a mass ratio of 1:0.8:0.7:0.03, heated at 150°C for 20 min, heated to 185°C, stirred at 85 rpm for 1 h, heated to 260°C and stirred in vacuum for 20 min, cooled naturally to room temperature, and sliced ​​to obtain modified polyester slices; modified polyester slices, modified zinc-loaded nano-alumina and polyethylene glycol 2000 were mixed in a mass ratio of 1:0.04:0.02, and melt-spun using a multifunctional flexible high-speed spinning machine at 255°C in the first zone, 285°C in the second zone, 285°C in the third zone, 285°C in the metering pump temperature, 285°C in the elbow temperature, 285°C in the box temperature, 37 spinneret holes, 11 Hz in the side blowing power, 21 Hz in the oil pump power, 9 MPa in the assembly pressure, and 850 m / min in the winding speed to obtain spun fibers; (4) Hydrogen-containing silicone oil and chloroplatinic acid are mixed in a mass ratio of 1:0.03 to obtain a hydrogen-containing silicone oil finishing solution; the spun fiber is soaked in the hydrogen-containing silicone oil finishing solution for 2 hours and then taken out, aired until no liquid drops for 20 seconds, allowed to stand at 80°C for 6 hours, washed with deionized water for 5 times, and dried at 65°C for 8 hours to obtain a modified fiber; the modified fiber is twisted and twisted, and plain woven on a small sample loom under the conditions of an online density of 78, a warp density of 650 strands / 10 cm, and a weft density of 400 strands / 10 cm to obtain a precursor fabric; a 2% mass fraction of 3-bromopropyltrimethylammonium bromide aqueous solution is sprayed on the outer surface of the precursor fabric, allowed to stand at 70°C for 11 hours, washed with deionized water for 5 times, and dried at 65°C for 12 hours to obtain a moisture-conducting and cool fabric for sportswear.

[0026] Comparative Example 1: A method for preparing a moisture-conducting and cooling fabric for sportswear, the method comprising the following preparation steps: (1) Porous nano-alumina powder, chloromethyltrimethoxysilane and anhydrous ethanol were mixed in a mass ratio of 1:0.015:15, ultrasonically dispersed for 25 minutes, stirred at 80°C and 150 rpm for 5 hours, naturally cooled to room temperature and filtered, and dried at 45°C for 5 hours to obtain pre-modified nano-alumina; pre-modified nano-alumina, 2,6-pyridine dimethanol, 3,6-dichloro-4-vinylpyridazine, sodium hydroxide and deionized water were mixed in a mass ratio of 1:1.5:1.8:5:1000, ultrasonically dispersed for 30 minutes, stirred at 35°C and 150 rpm for 6 hours, and a 37% hydrochloric acid solution with a mass fraction of 15 times the mass of the pre-modified nano-alumina was added, ultrasonically dispersed again for 30 minutes, filtered, washed with deionized water and anhydrous ethanol for 4 times respectively, and dried at 65°C for 12 hours to obtain modified nano-alumina; (2) Mix diethyl (formylmethyl) phosphate, 4-methylpyridine and n-butanol in a mass ratio of 1:0.55:7, heat to 110°C at 350 rpm in a nitrogen atmosphere, add pyridine in an amount of 0.2 times the mass of diethyl (formylmethyl) phosphate, continue stirring for 80 h, add deionized water in an amount of 150 times the mass of diethyl (formylmethyl) phosphate, stir until the mass of the precipitated solid remains unchanged, filter, grind and sieve 50 mesh, wash with acetone 4 times, and dry at 55°C for 13 h to obtain a modified monomer; (3) Dimethyl terephthalate, modified monomer, ethylene glycol and ethylene glycol antimony were mixed in a mass ratio of 1:0.7:0.6:0.02, heated at 145°C for 25 min, heated to 180°C, stirred at 80 rpm for 2 h, heated to 250°C and stirred in vacuum for 25 min, cooled naturally to room temperature, and sliced ​​to obtain modified polyester slices; modified polyester slices, modified nano-alumina and polyethylene glycol 2000 were mixed in a mass ratio of 1:0 .03:0.015 mixed, melt spinning was performed using a multifunctional flexible high-speed spinning machine at 250°C in the first zone, 280°C in the second zone, 280°C in the third zone, 280°C in the metering pump, 280°C in the elbow, 280°C in the box, 36 holes in the spinneret, 10Hz in the side blowing power, 20Hz in the oil pump power, 7.5MPa in the component pressure, and 800m / min in the winding speed to obtain spun fibers; (4) Hydrogen-containing silicone oil and chloroplatinic acid are mixed in a mass ratio of 1:0.02 to obtain a hydrogen-containing silicone oil finishing solution; the spun fiber is soaked in the hydrogen-containing silicone oil finishing solution for 1.5 hours and then taken out, aired until no liquid drops for 15 seconds, allowed to stand at 75°C for 7 hours, washed with deionized water for 4 times, and dried at 60°C for 9 hours to obtain a modified fiber; the modified fiber is twisted and twisted, and plain woven on a small sample loom under the conditions of an online density of 77, a warp density of 600 strands / 10cm, and a weft density of 380 strands / 10cm to obtain a precursor fabric; a 1.5% mass fraction of 3-bromopropyltrimethylammonium bromide aqueous solution is sprayed on the outer surface of the precursor fabric, allowed to stand at 65°C for 12 hours, washed with deionized water for 4 times, and dried at 60°C for 13 hours to obtain a moisture-conducting and cool fabric for sportswear.

[0027] Comparative Example 2: A method for preparing a moisture-conducting and cooling fabric for sportswear, the method comprising the following preparation steps: (1) The porous nano-alumina powder and ethylene glycol were mixed at a mass ratio of 1:100, 10 mol / L sodium hydroxide solution was added to adjust the pH to 8, ultrasonic dispersion was performed for 30 min, 25 times the mass of the porous nano-alumina powder was added with a saturated zinc nitrate alcohol solution, stirred at 50°C and 150 rpm for 8 h, cooled naturally to room temperature and centrifuged, washed with anhydrous ethanol for 4 times, and dried at 50°C for 9 h to obtain zinc-loaded nano-alumina; zinc-loaded nano-alumina, chloromethyltrimethoxysilane and anhydrous ethanol were mixed at a mass ratio of 1:0.015:15, ultrasonic dispersion was performed for 25 min, stirred at 80°C and 150 rpm for 5 h, cooled naturally to room temperature and filtered, and dried at 45°C for 5 h to obtain pre-modified zinc-loaded nano-alumina; (2) Mix diethyl (formylmethyl) phosphate, 4-methylpyridine and n-butanol in a mass ratio of 1:0.55:7, heat to 110°C at 350 rpm in a nitrogen atmosphere, add pyridine in an amount of 0.2 times the mass of diethyl (formylmethyl) phosphate, continue stirring for 80 h, add deionized water in an amount of 150 times the mass of diethyl (formylmethyl) phosphate, stir until the mass of the precipitated solid remains unchanged, filter, grind and sieve 50 mesh, wash with acetone 4 times, and dry at 55°C for 13 h to obtain a modified monomer; (3) Dimethyl terephthalate, modified monomer, ethylene glycol and ethylene glycol antimony were mixed in a mass ratio of 1:0.7:0.6:0.02, heated at 145°C for 25 min, heated to 180°C, stirred at 80 rpm for 2 h, heated to 250°C and stirred in vacuum for 25 min, cooled naturally to room temperature, and sliced ​​to obtain modified polyester slices; modified polyester slices, pre-modified zinc-loaded nano-alumina and polyethylene glycol 2000 were mixed in a mass ratio of 1:0.7:0.6:0.02. :0.03:0.015 mixed, using a multifunctional flexible high-speed spinning machine, melt spinning under the conditions of 250°C in the first zone, 280°C in the second zone, 280°C in the third zone, 280°C in the metering pump temperature, 280°C in the elbow temperature, 280°C in the box temperature, 36 holes in the spinneret, 10Hz in the side blowing power, 20Hz in the oil pump power, 7.5MPa in the component pressure, and 800m / min in the winding speed, to obtain spun fibers; (4) Hydrogen-containing silicone oil and chloroplatinic acid are mixed in a mass ratio of 1:0.02 to obtain a hydrogen-containing silicone oil finishing solution; the spun fiber is soaked in the hydrogen-containing silicone oil finishing solution for 1.5 hours and then taken out, aired until no liquid drops for 15 seconds, allowed to stand at 75°C for 7 hours, washed with deionized water for 4 times, and dried at 60°C for 9 hours to obtain a modified fiber; the modified fiber is twisted and twisted, and plain woven on a small sample loom under the conditions of an online density of 77, a warp density of 600 strands / 10cm, and a weft density of 380 strands / 10cm to obtain a precursor fabric; a 1.5% mass fraction of 3-bromopropyltrimethylammonium bromide aqueous solution is sprayed on the outer surface of the precursor fabric, allowed to stand at 65°C for 12 hours, washed with deionized water for 4 times, and dried at 60°C for 13 hours to obtain a moisture-conducting and cool fabric for sportswear.

[0028] Comparative Example 3: A method for preparing a moisture-conducting and cooling fabric for sportswear, the method comprising the following preparation steps: (1) Porous nano-alumina powder and ethylene glycol were mixed at a mass ratio of 1:100, 10 mol / L sodium hydroxide solution was added to adjust the pH to 8, ultrasonic dispersion was performed for 30 min, saturated zinc nitrate alcohol solution of 25 times the mass of porous nano-alumina powder was added, stirred at 50°C and 150 rpm for 8 h, cooled naturally to room temperature and centrifuged, washed with anhydrous ethanol for 4 times, and dried at 50°C for 9 h to obtain zinc-loaded nano-alumina; zinc-loaded nano-alumina, chloromethyltrimethoxysilane and anhydrous ethanol were mixed at a mass ratio of 1:0.015:15, ultrasonic dispersion was performed for 25 min, stirred at 80°C and 150 rpm for 5 h, and dried at 50°C for 9 h. Then cool to room temperature and filter, dry at 45°C for 5h to obtain pre-modified zinc-loaded nano-alumina; mix the pre-modified zinc-loaded nano-alumina, 2,6-pyridine dimethanol, 3,6-dichloro-4-vinyl pyridazine, sodium hydroxide and deionized water in a mass ratio of 1:1.5:1.8:5:1000, ultrasonicate for 30min, stir at 35°C and 150rpm for 6h, add a 37% hydrochloric acid solution with a mass fraction of 15 times the mass of the pre-modified zinc-loaded nano-alumina, ultrasonicate for 30min again, filter, wash with deionized water and anhydrous ethanol for 4 times respectively, and dry at 65°C for 12h to obtain modified zinc-loaded nano-alumina; (2) Dimethyl terephthalate, ethylene glycol and ethylene glycol antimony were mixed in a mass ratio of 1:0.6:0.02, heated at 145°C for 25 min, heated to 180°C, stirred at 80 rpm for 2 h, heated to 250°C and stirred in vacuum for 25 min, cooled naturally to room temperature, and sliced ​​to obtain polyester slices; polyester slices, modified zinc-loaded nano-alumina and polyethylene glycol 2000 were mixed in a mass ratio of 1:0.03:0.015, and melt-spun using a multifunctional flexible high-speed spinning machine at 250°C in zone 1, 280°C in zone 2, 280°C in zone 3, 280°C in metering pump temperature, 280°C in elbow temperature, 280°C in box temperature, 36 spinneret holes, 10 Hz in side blowing power, 20 Hz in oil pump power, 7.5 MPa in assembly pressure, and 800 m / min in winding speed to obtain spun fibers; (3) Hydrogen-containing silicone oil and chloroplatinic acid are mixed in a mass ratio of 1:0.02 to obtain a hydrogen-containing silicone oil finishing solution; the spun fiber is soaked in the hydrogen-containing silicone oil finishing solution for 1.5 hours and then taken out, aired until no liquid drops for 15 seconds, allowed to stand at 75°C for 7 hours, washed with deionized water for 4 times, and dried at 60°C for 9 hours to obtain a modified fiber; the modified fiber is twisted and twisted, and plain woven on a small sample loom under the conditions of an online density of 77, a warp density of 600 strands / 10cm, and a weft density of 380 strands / 10cm to obtain a precursor fabric; a 1.5% mass fraction of 3-bromopropyltrimethylammonium bromide aqueous solution is sprayed on the outer surface of the precursor fabric, allowed to stand at 65°C for 12 hours, washed with deionized water for 4 times, and dried at 60°C for 13 hours to obtain a moisture-conducting and cool fabric for sportswear.

[0029] Comparative Example 4: A method for preparing a moisture-conducting and cooling fabric for sportswear, the method comprising the following preparation steps: (1) Porous nano-alumina powder and ethylene glycol were mixed at a mass ratio of 1:100, 10 mol / L sodium hydroxide solution was added to adjust the pH to 8, ultrasonic dispersion was performed for 30 min, saturated zinc nitrate alcohol solution of 25 times the mass of porous nano-alumina powder was added, stirred at 50°C and 150 rpm for 8 h, cooled naturally to room temperature and centrifuged, washed with anhydrous ethanol for 4 times, and dried at 50°C for 9 h to obtain zinc-loaded nano-alumina; zinc-loaded nano-alumina, chloromethyltrimethoxysilane and anhydrous ethanol were mixed at a mass ratio of 1:0.015:15, ultrasonic dispersion was performed for 25 min, stirred at 80°C and 150 rpm for 5 h, and dried at 50°C for 9 h. Then cool to room temperature and filter, dry at 45°C for 5h to obtain pre-modified zinc-loaded nano-alumina; mix the pre-modified zinc-loaded nano-alumina, 2,6-pyridine dimethanol, 3,6-dichloro-4-vinyl pyridazine, sodium hydroxide and deionized water in a mass ratio of 1:1.5:1.8:5:1000, ultrasonicate for 30min, stir at 35°C and 150rpm for 6h, add a 37% hydrochloric acid solution with a mass fraction of 15 times the mass of the pre-modified zinc-loaded nano-alumina, ultrasonicate for 30min again, filter, wash with deionized water and anhydrous ethanol for 4 times respectively, and dry at 65°C for 12h to obtain modified zinc-loaded nano-alumina; (2) Mix diethyl (formylmethyl) phosphate, 4-methylpyridine and n-butanol in a mass ratio of 1:0.55:7, heat to 110°C at 350 rpm in a nitrogen atmosphere, add pyridine in an amount of 0.2 times the mass of diethyl (formylmethyl) phosphate, continue stirring for 80 h, add deionized water in an amount of 150 times the mass of diethyl (formylmethyl) phosphate, stir until the mass of the precipitated solid remains unchanged, filter, grind and sieve 50 mesh, wash with acetone 4 times, and dry at 55°C for 13 h to obtain a modified monomer; (3) Dimethyl terephthalate, modified monomer, ethylene glycol and ethylene glycol antimony were mixed in a mass ratio of 1:0.7:0.6:0.02, heated at 145°C for 25 min, heated to 180°C, stirred at 80 rpm for 2 h, heated to 250°C and stirred in vacuum for 25 min, cooled naturally to room temperature, and sliced ​​to obtain modified polyester slices; modified polyester slices, modified zinc-loaded nano-alumina and polyethylene glycol 2000 were mixed in a mass ratio of 1:0.7:0.6:0.02. 0.03:0.015 was mixed, and melt spinning was performed using a multifunctional flexible high-speed spinning machine at 250°C in the first zone, 280°C in the second zone, 280°C in the third zone, 280°C in the metering pump, 280°C in the elbow, 280°C in the box, 36 holes in the spinneret, 10Hz in the side blowing power, 20Hz in the oil pump power, 7.5MPa in the component pressure, and 800m / min in the winding speed to obtain spun fibers; (4) Mix hydrogen-containing silicone oil and chloroplatinic acid in a mass ratio of 1:0.02 to obtain a hydrogen-containing silicone oil finishing solution; soak the spun fiber in the hydrogen-containing silicone oil finishing solution for 1.5 hours, take it out, dry it until no liquid drops for 15 seconds, stand it at 75°C for 7 hours, wash it with deionized water for 4 times, and dry it at 60°C for 9 hours to obtain a modified fiber; twist the modified fiber together, and use a small sample loom to weave it in plain weave under the conditions of line density 77, warp density 600 strands / 10cm, and weft density 380 strands / 10cm to obtain a moisture-conducting and cool fabric for sportswear.

[0030] Comparative Example 5: A method for preparing a moisture-conducting and cooling fabric for sportswear, the method comprising the following preparation steps: (1) Porous nano-alumina powder and ethylene glycol were mixed at a mass ratio of 1:100, 10 mol / L sodium hydroxide solution was added to adjust the pH to 8, ultrasonic dispersion was performed for 30 min, saturated zinc nitrate alcohol solution of 25 times the mass of porous nano-alumina powder was added, stirred at 50°C and 150 rpm for 8 h, cooled naturally to room temperature and centrifuged, washed with anhydrous ethanol for 4 times, and dried at 50°C for 9 h to obtain zinc-loaded nano-alumina; zinc-loaded nano-alumina, chloromethyltrimethoxysilane and anhydrous ethanol were mixed at a mass ratio of 1:0.015:15, ultrasonic dispersion was performed for 25 min, stirred at 80°C and 150 rpm for 5 h, and dried at 50°C for 9 h. Then cool to room temperature and filter, dry at 45°C for 5h to obtain pre-modified zinc-loaded nano-alumina; mix the pre-modified zinc-loaded nano-alumina, 2,6-pyridine dimethanol, 3,6-dichloro-4-vinyl pyridazine, sodium hydroxide and deionized water in a mass ratio of 1:1.5:1.8:5:1000, ultrasonicate for 30min, stir at 35°C and 150rpm for 6h, add a 37% hydrochloric acid solution with a mass fraction of 15 times the mass of the pre-modified zinc-loaded nano-alumina, ultrasonicate for 30min again, filter, wash with deionized water and anhydrous ethanol for 4 times respectively, and dry at 65°C for 12h to obtain modified zinc-loaded nano-alumina; (2) Mix diethyl (formylmethyl) phosphate, 4-methylpyridine and n-butanol in a mass ratio of 1:0.55:7, heat to 110°C at 350 rpm in a nitrogen atmosphere, add pyridine in an amount of 0.2 times the mass of diethyl (formylmethyl) phosphate, continue stirring for 80 h, add deionized water in an amount of 150 times the mass of diethyl (formylmethyl) phosphate, stir until the mass of the precipitated solid remains unchanged, filter, grind and sieve 50 mesh, wash with acetone 4 times, and dry at 55°C for 13 h to obtain a modified monomer; (3) Dimethyl terephthalate, modified monomer, ethylene glycol and ethylene glycol antimony were mixed in a mass ratio of 1:0.7:0.6:0.02, heated at 145°C for 25 min, heated to 180°C, stirred at 80 rpm for 2 h, heated to 250°C and stirred in vacuum for 25 min, naturally cooled to room temperature, and sliced ​​to obtain modified polyester slices; the modified polyester slices and modified zinc-loaded nano-alumina were mixed in a mass ratio of 1:0.03, and melt-spun using a multifunctional flexible high-speed spinning machine at 250°C in the first zone, 280°C in the second zone, 280°C in the third zone, 280°C in the metering pump temperature, 280°C in the elbow temperature, 280°C in the box temperature, 36 spinneret holes, 10 Hz in the side blowing power, 20 Hz in the oil pump power, 7.5 MPa in the component pressure, and 800 m / min in the winding speed to obtain spun fibers; (4) Hydrogen-containing silicone oil and chloroplatinic acid are mixed in a mass ratio of 1:0.02 to obtain a hydrogen-containing silicone oil finishing solution; the spun fiber is soaked in the hydrogen-containing silicone oil finishing solution for 1.5 hours and then taken out, aired until no liquid drops for 15 seconds, allowed to stand at 75°C for 7 hours, washed with deionized water for 4 times, and dried at 60°C for 9 hours to obtain a modified fiber; the modified fiber is twisted and twisted, and plain woven on a small sample loom under the conditions of an online density of 77, a warp density of 600 strands / 10cm, and a weft density of 380 strands / 10cm to obtain a precursor fabric; a 1.5% mass fraction of 3-bromopropyltrimethylammonium bromide aqueous solution is sprayed on the outer surface of the precursor fabric, allowed to stand at 65°C for 12 hours, washed with deionized water for 4 times, and dried at 60°C for 13 hours to obtain a moisture-conducting and cool fabric for sportswear.

[0031] Test Example 1: 1. Moisture conductivity Test method: The moisture-conducting and cooling fabrics for sportswear obtained in each embodiment and the comparative example were tested for moisture permeability using a YG(B)216G fabric moisture permeability tester according to GB / T12704; 2. Cooling effect Test method: The moisture-conducting and cool fabrics for sportswear obtained in each embodiment and the comparative example were balanced in a constant temperature and humidity chamber at 20°C and 65% for 24 hours according to GB / T6529, and the maximum transient heat flux Q of the fabric was tested by a KES-F7 tester with a temperature difference of 20°C on the upper layer and 30°C on the lower layer using a heated copper plate. max; 3. Flame retardancy Test method: The moisture-conducting and cooling fabrics for sportswear obtained in each embodiment and the comparative example were tested for limiting oxygen index using an FTA limiting oxygen index instrument according to GB / T5454.

[0032] Table 1 below shows the analysis results of the moisture conduction, cooling feeling and flame retardant properties of the moisture conduction, cooling feeling fabrics for sportswear of Examples 1 to 3 of the present invention and Comparative Examples 1 to 5.

[0033]

[0034] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 1, it can be found that the moisture-conducting and cooling fabric for sportswear prepared by the present invention has good moisture-conducting and cooling properties and flame retardant properties.

[0035] By comparison, the limiting oxygen index of Examples 1, 2, and 3 is higher than that of Comparative Example 2, indicating that 2,6-pyridine dimethanol and 3,6-dichloro-4-vinyl pyridazine are polymerized and grafted on the surface of the porous nano-alumina. During the combustion process, the pyridazine ring can produce nitrides, nitrogen-containing free radicals and other substances, which react with the free radicals in the combustion process to inhibit the continuation of the combustion reaction and improve the flame retardant properties of the moisture-conducting and cool fabric.

[0036] By comparison, the limiting oxygen index of Examples 1, 2, and 3 is higher than that of Comparative Example 3, indicating that a modified monomer containing a carbon-carbon double bond is obtained by a condensation reaction of methyl and formaldehyde under the catalysis of pyridine, participates in the polymerization of the polyester main chain, introduces phosphorus, and reacts with the free radicals generated during the combustion process to form a stable carbon layer, which blocks oxygen, inhibits the spread of flame, and improves the flame retardant properties of the moisture-conducting and cool fabric.

[0037] By comparison, the moisture permeability of Examples 1, 2, and 3 is higher than that of Comparative Example 4, which shows that the finishing with hydrogen silicone oil enhances the hydrophobic ability of the fiber. After being woven into the fabric, it is finished on one side with 3-bromopropyltrimethylammonium bromide, and trimethylammonium bromide ions are used as the hydrophilic end to form a unidirectional moisture-conducting structure with a hydrophobic inner layer and a hydrophilic outer layer, thereby improving the moisture-conducting performance of the moisture-conducting and cool fabric.

[0038] By comparison, the moisture permeability and maximum transient heat flux of Examples 1, 2, and 3 are higher than those of Comparative Example 5, which indicates that polyethylene glycol 2000 is used as a porogen to form a pore structure and improve the moisture-conducting and cooling performance of the moisture-conducting and cooling fabric.

[0039] Test Example 2: 1. Mechanical properties Test method: The moisture-conducting and cooling fabrics for sportswear obtained in each embodiment and the comparative example were made into 20 cm × 5 cm strips according to GB / T3923, and the warp breaking strength was tested under the conditions of a clamping distance of 100 mm and a tensile speed of 100 mm / min; 2. Antibacterial Test method: Take 0.1g of the moisture-conducting and cooling fabric for sportswear obtained in each embodiment and the comparative example, cut them into pieces as test samples, and add the sample to a concentration of 10 6 CFU / ml of bacterial solution, after 18h of culture, calculate the inhibition rate P 0 =(blank bacteria count - sample bacteria count) / blank bacteria count*100%; 3. Long-lasting antibacterial properties Test method: Take samples of 10 cm × 10 cm in size from the moisture-conducting and cool fabrics for sportswear obtained in each embodiment and the comparative example, wash them at 40°C for 45 min and then dry them, repeat the washing and drying 20 times, and then take 0.1 g of each sample and cut them into pieces as test samples. According to GB / T20944, take Gram-negative bacteria Escherichia coli as the experimental object, add the sample to a concentration of 10 6 CFU / ml of bacterial solution, after 18h of culture, the antibacterial rate P 1 =(blank bacteria count - sample bacteria count) / blank bacteria count*100%, calculate the antibacterial retention rate = P 1 / P 0 *100%.

[0040] Table 2 below shows the analysis results of the antibacterial and mechanical properties of the moisture-conducting and cooling fabrics for sportswear of Examples 1 to 3 of the present invention and Comparative Examples 1 to 5.

[0041]

[0042] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 2, it can be found that the moisture-conducting and cooling fabric for sportswear prepared by the present invention has good antibacterial and mechanical properties.

[0043] By comparison, the antibacterial rates of Examples 1, 2, and 3 are higher than those of Comparative Example 1, which indicates that zinc ions are loaded in the pores of porous nano-alumina, and the zinc ions interact with the negative ions of bacterial cells to cause abnormal enzyme and protein mechanisms in bacterial cells, destroy cell metabolism, and improve the antibacterial properties of the moisture-conducting and cool fabric.

[0044] By comparison, Examples 1, 2, and 3 have higher warp breaking strength, antibacterial rate, and antibacterial retention rate than Comparative Example 2, indicating that 2,6-pyridine dimethanol and 3,6-dichloro-4-vinylpyridazine are polymerized and grafted on the surface of porous nano-alumina, and the pyridine ring can complex zinc ions to achieve a sustained release effect, thereby improving the long-lasting antibacterial property of the moisture-conducting and cool fabric; hydrogen-containing silicone oil is used for post-finishing of the spun fibers, and a silylation reaction is used to react with the carbon-carbon double bonds on the modified zinc-loaded nano-alumina to form a cross-linked network, thereby improving the mechanical properties of the moisture-conducting and cool fabric; 3-bromopropyltrimethylammonium bromide is used for single-sided finishing to form a quaternary ammonium salt with the nitrogen heterocycle on the modified zinc-loaded nano-alumina, thereby increasing the positive charge density, enhancing the antibacterial activity, and further improving the antibacterial property of the moisture-conducting and cool fabric.

[0045] By comparison, Examples 1, 2, and 3 have higher warp breaking strength and antibacterial rate than Comparative Example 3, which shows that the spun fibers are post-finished with hydrogenated silicone oil, and the hydrogen silylation reaction is used to react with the carbon-carbon double bonds on the modified polyester slices to form a cross-linked network, thereby improving the mechanical properties of the moisture-conducting and cool fabric; 3-bromopropyltrimethylammonium bromide is used for single-sided finishing to form a quaternary ammonium salt with the nitrogen heterocycle on the modified polyester, thereby increasing the positive charge density, enhancing the antibacterial activity, and improving the antibacterial properties of the moisture-conducting and cool fabric.

[0046] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A moisture-conducting and cooling fabric for sportswear, characterized in that: The moisture-conducting and cool fabric for sportswear is obtained by weaving a precursor fabric after the reaction of spun fibers and hydrogen-containing silicone oil, and then reacting with 3-bromopropyltrimethylammonium bromide; the spun fibers are obtained by mixing and spinning modified polyester chips, modified zinc-loaded nano-alumina and polyethylene glycol 2000; the modified polyester chips are obtained by reacting diethyl (formylmethyl) phosphate with 4-methylpyridine, and then reacting with dimethyl terephthalate and ethylene glycol; the modified zinc-loaded nano-alumina is obtained by loading zinc ions on porous nano-alumina, grafting chloromethyltrimethoxysilane, and then reacting with 2,6-pyridine dimethanol and 3,6-dichloro-4-vinylpyridazine.

2. A method for preparing a moisture-conducting and cool fabric for sportswear, characterized in that: The method comprises the following preparation steps: (1) Mixing porous nano-alumina powder and zinc nitrate to obtain zinc-loaded nano-alumina; mixing zinc-loaded nano-alumina, chloromethyltrimethoxysilane and anhydrous ethanol to obtain pre-modified zinc-loaded nano-alumina; mixing pre-modified zinc-loaded nano-alumina, 2,6-pyridine dimethanol, 3,6-dichloro-4-vinylpyridazine, sodium hydroxide and deionized water to obtain modified zinc-loaded nano-alumina; (2) mixing diethyl (formylmethyl) phosphate, 4-methylpyridine and n-butanol to obtain a modified monomer; (3) Dimethyl terephthalate, modified monomer, ethylene glycol and ethylene glycol antimony are mixed to obtain modified polyester chips; modified polyester chips, modified zinc-loaded nano-alumina and polyethylene glycol 2000 are mixed to obtain spinning fibers using a multifunctional flexible high-speed spinning machine; (4) finishing the spun fiber with a hydrogen-containing silicone oil finishing liquid to obtain a modified fiber; The modified fibers are twisted and woven on a sample loom to obtain a precursor fabric; an aqueous solution of 3-bromopropyltrimethylammonium bromide is sprayed on the outer surface of the precursor fabric to obtain a moisture-conducting and cool fabric for sportswear.

3. The method for preparing a moisture-conducting cool fabric for sportswear according to claim 2, characterized in that: The zinc-loaded nano-alumina in step (1) is prepared by mixing porous nano-alumina powder and ethylene glycol in a mass ratio of 1:(95-105), adding 9-11 mol / L sodium hydroxide solution to adjust the pH to 7.5-8.5, ultrasonically dispersing for 25-35 minutes, adding saturated zinc nitrate alcohol solution in an amount of 20-30 times the mass of the porous nano-alumina powder, stirring at 45-55° C. and 100-200 rpm for 7-9 hours, naturally cooling to room temperature and then centrifuging, washing with anhydrous ethanol for 3-5 times, and drying at 45-55° C. for 8-10 hours.

4. The method for preparing a moisture-conducting cool fabric for sportswear according to claim 2, characterized in that: The pre-modified zinc-loaded nano-alumina in step (1) is prepared by mixing zinc-loaded nano-alumina, chloromethyltrimethoxysilane and anhydrous ethanol in a mass ratio of 1: (0.01-0.02): (10-20), ultrasonically dispersing for 20-30 minutes, stirring at 70-90° C. and 100-200 rpm for 4-6 hours, naturally cooling to room temperature, filtering, and drying at 40-50° C. for 4-6 hours.

5. The method for preparing a moisture-conducting cool fabric for sportswear according to claim 2, characterized in that: The modified zinc-loaded nano-alumina in step (1) is prepared by mixing pre-modified zinc-loaded nano-alumina, 2,6-pyridine dimethanol, 3,6-dichloro-4-vinylpyridazine, sodium hydroxide and deionized water in a mass ratio of 1: (1-2): (1.7-1.9): (4-6): (950-1050), ultrasonically treating for 25-35 minutes, stirring at 30-40° C. and 100-200 rpm for 5-7 hours, adding a hydrochloric acid solution having a mass fraction of 36%-38% which is 10-20 times the mass of the pre-modified zinc-loaded nano-alumina, ultrasonically treating for 25-35 minutes again, filtering, washing with deionized water and anhydrous ethanol for 3-5 times respectively, and drying at 60-70° C. for 11-13 hours to obtain the modified zinc-loaded nano-alumina.

6. The method for preparing a moisture-conducting cool fabric for sportswear according to claim 2, characterized in that: The modified monomer in step (2) is prepared by mixing diethyl (formylmethyl) phosphate, 4-methylpyridine and n-butanol in a mass ratio of 1: (0.5-0.6): (6-8), heating to 105-115° C. at 300-400 rpm in a nitrogen atmosphere, adding pyridine in an amount of 0.1-0.3 times the mass of diethyl (formylmethyl) phosphate, continuing stirring for 79-81 hours, adding deionized water in an amount of 100-200 times the mass of diethyl (formylmethyl) phosphate, stirring until the mass of the precipitated solid remains unchanged, filtering, grinding and sieving 40-60 mesh, washing with acetone for 3-5 times, and drying at 50-60° C. for 12-14 hours.

7. The method for preparing a moisture-conducting cool fabric for sportswear according to claim 2, characterized in that: The spun fiber in step (3) is prepared by mixing dimethyl terephthalate, modified monomer, ethylene glycol and ethylene glycol antimony in a mass ratio of 1: (0.6-0.8): (0.5-0.7): (0.01-0.03), heating at 140-150° C. for 20-30 min, heating to 175-185° C., stirring at 75-85 rpm for 1-3 h, heating to 240-260° C., stirring under vacuum for 20-30 min, naturally cooling to room temperature, taking out slices to obtain modified polyester slices; and mixing the modified polyester slices, modified zinc-loaded nano-alumina and polyethylene glycol 2000 in a mass ratio of 1: (0.02-0.04): (0.01-0.02), and melt spinning using a multifunctional flexible high-speed spinning machine to obtain the obtained fiber.

8. The method for preparing a moisture-conducting cool fabric for sportswear according to claim 7, characterized in that: The melt spinning parameters are: spinneret hole number 35~37 holes, side blowing power 9~11Hz, oil pump power 19~21Hz, assembly pressure 6~9MPa, winding speed 750~850m / min, zone 1 245~255℃, zone 275~285℃, zone 3 275~285℃, metering pump temperature 275~285℃, elbow temperature 275~285℃, box temperature 275~285℃.

9. The method for preparing a moisture-conducting cool fabric for sportswear according to claim 2, characterized in that: The moisture-conducting and cool fabric for sportswear in step (4) is prepared by soaking the spun fiber in a hydrogenated silicone oil finishing solution for 1 to 2 hours, taking it out, airing it until no liquid drops for 10 to 20 seconds, standing it at 70 to 80° C. for 6 to 8 hours, washing it with deionized water for 3 to 5 times, and drying it at 55 to 65° C. for 8 to 10 hours to obtain a modified fiber; The modified fibers are then twisted and plain woven on a sample loom at an online density of 76-78, a warp density of 550-650 strands / 10cm, and a weft density of 360-400 strands / 10cm to obtain a precursor fabric; a 1%-2% by mass aqueous solution of 3-bromopropyltrimethylammonium bromide is sprayed on the outer surface of the precursor fabric, and the fabric is allowed to stand at 60-70°C for 11-13h, washed with deionized water for 3-5 times, and dried at 55-65°C for 12-14h.

10. The method for preparing a moisture-conducting and cool fabric for sportswear according to claim 9, characterized in that: The hydrogen-containing silicone oil finishing liquid is obtained by mixing hydrogen-containing silicone oil and chloroplatinic acid in a mass ratio of 1: (0.01-0.03).

Citation Information

Cited By

  • Antibacterial and deodorant blended fabric, preparation method thereof and application of antibacterial and deodorant blended fabric in underwear

    CN119843490A

  • Cool washing-resistant bio-based nylon 56 fabric and preparation method thereof

    CN120211109A